(untitled) (GAIMS Journal of Medical Sciences, 2024)
Background: Honeycomb gallbladder (GB) is a rare condition characterized by multiple septations in the GB wall, giving it a honeycomb appearance. First described by Knetsch in 1952, this anomaly is typically congenital but can also be acquired. Patients with a honeycomb GB often present with a variety of symptoms, the most common being abdominal pain. Case Description: We present the case of a 62-year-old female with a history of symptomatic chronic calculus cholecystitis. She underwent a laparoscopic cholecystectomy, which resolved her symptoms. Preoperative ultrasound imaging showed no evidence of multiple septations; however, post-operative examination revealed a multiseptated gallbladder. Conclusions: Honeycomb GB is an unusual presentation. Among the theories explaining multiseptated GB, one suggests that chronic calculus cholecystitis leads to extensive denudation of the epithelial lining, causing fibrosis and calcification beneath, which results in contraction. Our case supports this theory, as these pathological changes likely contributed to the honeycomb appearance. While medical management typically focuses on symptomatic relief, cholecystectomy has been shown to completely resolve symptoms.